2020
DOI: 10.1111/aji.13228
|View full text |Cite
|
Sign up to set email alerts
|

Significance of mast cells in spermatogenesis, implantation, pregnancy, and abortion: Cross talk and molecular mechanisms

Abstract: Both subsets of MCs including MCTC (tryptase‐positive, chymase‐positive) and MCT (tryptase‐positive, chymase‐negative) are present in the testis and epididymis. Increased number of MCs, higher levels of MC‐released tryptase in testis and seminal plasma of males with fertility problems, and promoting sperm motility in individuals with oligozoospermia after using MC blockers provide evidence that MCs may play a role in male infertility/subfertility disturbances. MC‐released tryptase and histamine contribute to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 92 publications
0
28
0
Order By: Relevance
“…In addition, the expression of PD-L1 on both CD45 + and CD45 − subpopulations is significantly downregulated in the anti-PD-L1 groups, hinting possible disruption of the inherent immunosuppressive circumstances ( Figure 4c ). Considering that IgG antibodies can trigger the activation of the mast cells and the resultant histamine release may affect the steroidogenesis in Leydig cells, 27 , 28 both the infiltration of mast cells in the testes and the histamine levels in the blood was analyzed. As shown in Figure 4d , there is no substantial difference in the infiltration of mast cells after treatment with anti-PD-L1, while the blood histamine levels in the anti-PD-L1 group are significantly reduced.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the expression of PD-L1 on both CD45 + and CD45 − subpopulations is significantly downregulated in the anti-PD-L1 groups, hinting possible disruption of the inherent immunosuppressive circumstances ( Figure 4c ). Considering that IgG antibodies can trigger the activation of the mast cells and the resultant histamine release may affect the steroidogenesis in Leydig cells, 27 , 28 both the infiltration of mast cells in the testes and the histamine levels in the blood was analyzed. As shown in Figure 4d , there is no substantial difference in the infiltration of mast cells after treatment with anti-PD-L1, while the blood histamine levels in the anti-PD-L1 group are significantly reduced.…”
Section: Resultsmentioning
confidence: 99%
“…Available data regarding MCs in the testis abounds exquisite reviews on humans [16,33,130] and a comprehensive review on MCs in the nonmammalian vertebrates [42], including the presence of MCs in the testes of birds, frogs, and lizards. A comprehensive review on the mammalian testicular and epididymal MC has not been found written from the perspective of method and result comparison in the available literature and may have a significant impact in drawing the attention of future authors to crucial problems in MC analysis.…”
Section: Discussionmentioning
confidence: 99%
“…ACA induces abortion via promoting thrombosis, damaging trophoblasts, and activating inflammation and the complement response by targeting β 2-GPI [ 14 , 15 ]. TNF- α plays a critical role in the physiology and pathology of pregnancies by regulating the immune balance at the maternal-fetal interface [ 16 , 17 ]. Excessive TNF- α causes thrombosis and TNF- α can activate immunocompetent cells in the decidual stroma, induce immune-mediated destruction and immune rejection, hinder the maintenance of pregnancy and embryo implantation, disrupt the homeostasis of the maternal uterine environment, and cause spontaneous abortion [ 16 , 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%